Trajectories and nuclear arrangement of PML bodies are influenced by A-type lamin deficiency - Stixová, Lenka; Matula, Pavel; Kozubek, Stanislav; Gombitová, Adriána; Cmarko, Dušan; Raška, Ivan; Bártová, Eva (Biology of the cell, 2012)
BACKGROUND INFORMATION: Promyelocytic leukaemia (PML) bodies are specific nuclear structures with functional significance for acute promyelocytic leukaemia. In this study, we analysed the trajectories of PML bodies using single-particle tracking. RESULTS: We observed that the recovery of PML protein after photobleaching was ATP dependent in both wild-type (wt) and A-type lamin-deficient cells. The movement of PML bodies was faster and the nuclear area occupied by particular PML bodies was larger in A-type lamin-deficient fibroblasts compared with their wt counterparts. Moreover, dysfunction of the LMNA gene increased the frequency of mutual interactions between individual PML bodies and influenced the morphology of these domains at the ultrastructural level. As a consequence of A-type lamin deficiency, PML protein accumulated in nuclear blebs and frequently appeared at the nuclear periphery. CONCLUSIONS: We suggest that the physiological function of lamin A proteins is important for events that occur in the compartment of PML bodies. This observation was confirmed in other experimental models characterised by lamin changes, including apoptosis or the differentiation of mouse embryonic stem cells.
Keywords: Intranuclear Inclusion Bodies; apoptóza; FRAP; Green Fluorescent Proteins; Apoptosis; fibroblasty; Embryo, Mammalian; Kinetics; zelené fluorescenční proteiny; myši; kinetika; Mice; akutní promyelocytární leukemie; Fluorescence Recovery After Photobleaching; intranukleární inkluzní tělíska; Embryonic Stem Cells; zvířata; Animals; Fibroblasts; Lamin Type A; embryo savčí; Reproducibility of Results; reprodukovatelnost výsledků; embryonální kmenové buňky; lamin typ A; Leukemia, Promyelocytic, Acute